2022
DOI: 10.1111/tid.13842
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, etiology, risk factors, and outcomes of pre‐engraftment bloodstream infections after first and second allogeneic hematopoietic cell transplantation

Abstract: Introduction:With an increasing number of allogeneic hematopoietic cell transplantations (allo-HCT) bloodstream infections (BSI) are still among the most common and serious complications. This study aimed to analyze the incidence, etiology, risk factors, and outcomes of pre-engraftment BSI after the first and the second allo-HCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
3
9
0
2
Order By: Relevance
“…Previous studies have also reported that Enterococcus spp. were the major causative pathogens after the second HSCT and that previous HSCT was a risk factor for BSI with Enterococcus spp., which is consistent with the results of the present study ( 1 , 2 , 25 ). The risk of enterococcal infection increases as the duration of neutropenia increases, and in the present study, the high number of CBTs (characterized by a prolonged period of neutropenia) may have contributed to this increase ( 6 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Previous studies have also reported that Enterococcus spp. were the major causative pathogens after the second HSCT and that previous HSCT was a risk factor for BSI with Enterococcus spp., which is consistent with the results of the present study ( 1 , 2 , 25 ). The risk of enterococcal infection increases as the duration of neutropenia increases, and in the present study, the high number of CBTs (characterized by a prolonged period of neutropenia) may have contributed to this increase ( 6 , 25 ).…”
Section: Discussionsupporting
confidence: 94%
“…The cumulative incidence of BSI at 30 days after the second HSCT was 36.5%, and this was an obvious increase compared with the cumulative incidence of BSI after the first HSCT. A study of 37 second-HSCT recipients [including 25 (67.6%) patients who underwent the second HSCT for graft failure] also reported a higher cumulative incidence of pre-engraftment BSI (35.1%) after the second HSCT than after the first HSCT ( 2 ). In another study that included 60 second-HSCT recipients [including 16 (27%) patients who underwent the second HSCT for graft failure], most bacterial infections, including BSI, occurred during the pre-engraftment period ( 1 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This corroborates with studies in the literature that report a smaller overall survival in carbapenem‐resistant K. pneumoniae ‐colonized patients when compared to noncolonized patients, with an approximate 35% survival rate in infected patients 37,38 . Other studies support that pre‐engraftment bloodstream infections caused by carbapenem‐resistant Gram‐negative bacteria are associated with extremely high nonrelapse mortality rates 39 . A positive rectal swab anticipated the onset of bacteremia in 12 of 13 cases of carbapenemase‐producing K. pneumoniae infections (92.3%), and all patients had at least one positive rectal swab.…”
Section: Discussionsupporting
confidence: 88%
“…37,38 Other studies support that preengraftment bloodstream infections caused by carbapenem-resistant Gram-negative bacteria are associated with extremely high nonrelapse mortality rates. 39 A positive rectal swab anticipated the onset of bacteremia in 12 of 13 cases of carbapenemase-producing K. pneumoniae infections (92.3%), and all patients had at least one positive rectal swab. This is a higher proportion than what was described in the literature 7 and justifies the need for active surveillance cultures.…”
Section: Discussionmentioning
confidence: 90%